The Silences of Ramana Maharshi: Self-enquiry and Liberation in Samkhya Yoga and Advaita Vedanta - Barua, Ankur (Religions of South Asia, 2016)
Both Samkhya-Yoga and Advaita Vedanta grapple with a conceptual tension which informs their understandings of spiritual practice--that while embodied selves seek liberation from the structures of worldly suffering, they are essentially the immutable reality which is never subject to any empirical ills. Though the metaphysical visions of these systems sharply diverge, Advaitins such as Samkara were able to appropriate from Samkhya-Yoga certain practices geared toward the yogic purification of the mind while rejecting its ontological scheme outlining a dualism between purusa and prakrti. By highlighting the complex relationship between Samkhya-Yoga and Samkara, we examine how it was creatively re-imagined by Ramana Maharshi who developed certain distinctive pedagogical styles centred around the liberating value of silence.